2023
DOI: 10.3390/su15107833
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Disintegration of Guilin Red Clay

Abstract: In order to study the disintegration characteristics of red clay under different moisture content and temperature, red clay taken from Guilin was prepared into samples with different moisture content, and the disintegration test of red clay was carried out by self-made test equipment. Considering the influence of water absorption and weight gain in red clay, a parallel water absorption test was carried out for each disintegration test, and the disintegration amount–time relationship curve was corrected with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Ruiz-Vera et al [18] considered that the soil disintegration rate is closely related to the initial moisture content. Liu et al [19] and Chen et al [20] investigated the impact of varying moisture levels on the disintegration of Guilin red clay and granite residual soil. However, they did not adequately consider the pore structure of the soil-rock mass.…”
Section: Introductionmentioning
confidence: 99%
“…Ruiz-Vera et al [18] considered that the soil disintegration rate is closely related to the initial moisture content. Liu et al [19] and Chen et al [20] investigated the impact of varying moisture levels on the disintegration of Guilin red clay and granite residual soil. However, they did not adequately consider the pore structure of the soil-rock mass.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [15,16] through the disintegration test of soft rock, that the disintegration of soft rock is a multiple fractal process, the introduction of fractal theory to get a quantitative description of the disintegration process of the red layer soft rock fractional dimensional indexes, the establishment of a mathematical model to simulate the disintegration of the red layer soft rock, and also pointed out that the nature of the red layer material is stable after the complete disintegration of the red layer, the treatment of the red sandstone in the actual engineering of a good reference. Liu et al [14] investigated the disintegration characteristics of red clay at different water contents and temperatures and found that the amount of disintegration decreased with increasing water content. Some scholars through the loess submerged disintegration test, found that the disintegration process of loess can be divided into three wider stages of wetting, softening and settling, explored the relationship between disintegration and influencing factors such as water content, temperature, salinity, etc., and discussed the effect of water content on the kinetic stability of loess [24,25,10,36].…”
Section: Introductionmentioning
confidence: 99%